2000
DOI: 10.1007/s11627-000-0043-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of transgenic cabbage (Brassica oleracea var. Capitata) for insect resistance by Agrobacterium tumefaciens-mediated transformation

Abstract: Transgenic head cabbage (Brassica oleracea var. capitata), resistant to diamondback moth (Plutella xylostella) larvae, was developed through Agrobacterium tumefaciens-mediated transformation with Bacillus thuringiensis (Bt) cry genes using a modified procedure. Factors important for transformation included cabbage cultivar; preculture and coculture of explants on a callus initiation medium; use of appropriate amount; and delay in initial application of selective agents. A total of 15 independent transformed li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…Due to successful introduction of genes coding for Bt toxins against insect pests in important crops such as cotton, maize and potato (AGBIOS, 2009), R&D activities in GM Brassica species toward insect resistance traits have been forced in recent years. In cabbage and oilseed rape, the expression of Bt toxins (Jin et al, 2000;Liu et al, 2008), harmful enzymes (Wang et al, 2005;Mulligan et al, 2006) and the regulation of insect gene expression through RNA interference (RNAi) (Baum et al, 2007) have been addressed. However, insect-resistant GM Brassica crops are not commercially available so far.…”
Section: Includementioning
confidence: 99%
“…Due to successful introduction of genes coding for Bt toxins against insect pests in important crops such as cotton, maize and potato (AGBIOS, 2009), R&D activities in GM Brassica species toward insect resistance traits have been forced in recent years. In cabbage and oilseed rape, the expression of Bt toxins (Jin et al, 2000;Liu et al, 2008), harmful enzymes (Wang et al, 2005;Mulligan et al, 2006) and the regulation of insect gene expression through RNA interference (RNAi) (Baum et al, 2007) have been addressed. However, insect-resistant GM Brassica crops are not commercially available so far.…”
Section: Includementioning
confidence: 99%
“…botrytis) (Cao et al, 1999;Metz et al, 1995), cabbage (B. oleracea var. capitata) (Jin et al, 2000), and Chinese cabbage (B. rapa L. subsp. chinensis) (Cho et al, 2001;Xiang et al, 1999), using the Bt cry1Ac gene designed to control diamondback moth.…”
Section: Introductionmentioning
confidence: 99%
“…In all the above cases, the regeneration capacity decreased when the age of the seedling was increased to more than 4 days. In one instance, it was found that 2 week old explants resulted in good regeneration in cabbage (Jin et al 2000). For hypocotyl sections, the older explants (8-10 days) have also been used for B. napus allowing a larger number of explants to be obtained per seedling (Maheshwari et al 2011).…”
Section: Age and Size Of The Explantsmentioning
confidence: 99%
“…In B. rapa and B. juncea, Chi and Pua (1989) and Chi (1990) reported that higher regeneration frequencies could be achieved if the explants were given an appropriate media and environmental conditions, thereby removing/reducing hyperhydricity. The factors found to affect hyperhydricity and tissue necrosis are the accumulation of ethylene and high humidity in culture vessels (de Block et al 1989), excessively rich media (Ziv 1991), Agrobacterium overgrowth/sensitivity (Jin et al 2000), and high doses of exogenous cytokinin and/or auxin (Kamal et al 2007). In B. napus (Cardoza and Stewart 2003), increasing the percentage of gelling agent (from 0.8% phytagar to 1.2%) in the shoot elongation medium reduced the relative humidity of the culture vessel and reduced the hyperhydricity.…”
Section: Hyperhydricity and Tissue Necrosismentioning
confidence: 99%